The effects of post‐learning alcohol ingestion on human motor memory consolidation - Hamel, Raphael; Demers, Olivier; Lepage, Jean‐Francois; Bernier, Pierre‐Michel (The European journal of neuroscience, 2022)
The neurochemical mechanisms underlying motor memory consolidation remain largely unknown. Based on converging work showing that ethyl alcohol retrogradely enhances declarative memory consolidation, this work tested the hypothesis that post‐learning alcohol ingestion would enhance motor memory consolidation. In a within‐subject and fully counterbalanced design, participants (n = 24; 12M; 12F) adapted to a gradually introduced visual deviation and ingested, immediately after adaptation, a placebo (PBO), a medium (MED) or high (HIGH) dose of alcohol. The alcohol doses were bodyweight‐ and gender‐controlled to yield peak breath alcohol concentrations of 0.00% in the PBO, ~0.05% in the MED and ~0.095% in the HIGH condition. Retention was evaluated 24 h later through reach aftereffects when participants were sober. The results revealed that retention levels were neither significantly nor meaningfully different in both the MED and HIGH conditions as compared to PBO (all absolute Cohen's dz values < ~0.2; small to negligible effects), indicating that post‐learning alcohol ingestion did not alter motor memory consolidation. Given alcohol's known pharmacological GABAergic agonist and NMDA antagonist properties, one possibility is that these neurochemical mechanisms do not decisively contribute to motor memory consolidation. As converging work demonstrated alcohol's retrograde enhancement of declarative memory, the present results suggest that distinct neurochemical mechanisms underlie declarative and motor memory consolidation. Elucidating the neurochemical mechanisms underlying the consolidation of different memory systems may yield insights into the effects of over‐the‐counter drugs on everyday learning and memory but also inform the development of pharmacological interventions seeking to alter human memory consolidation. Post‐learning ingestion of alcohol did not enhance motor memory consolidation of a gradual visuomotor adaptation task learned with the dominant hand as compared to placebo. Moreover, despite greatly differing breath alcohol concentrations, alcohol neither interfered with learning nor retention capabilities as compared to placebo, as assessed via visuomotor adaptation of the non‐dominant hand 1 h following alcohol ingestion.